Proteotranscriptomic analyses reveal distinct interferon-beta signaling pathways and therapeutic targets in choroidal neovascularization - Hu, Yuxiang; Qi, Siyi; Zhuang, Hong; Zhuo, Qiao; Liang, Yu; Kong, Hongyu; Zhao, Chen; Zhang, Shujie (Frontiers in Immunology, 2023)
To probe into the molecular mechanism underlying the onset of choroidal neovascularization (CNV), integrated transcriptomic and proteomic analyses of the retinas in mice with laser-induced CNV were performed by using RNA sequencing and tandem mass tag. In addition, the laser-treated mice received systemic interferon-β (IFN-β) therapy. The measurements of CNV lesion were acquired by confocal analysis of stained choroidal flat mounts. The proportions of T helper 17 (Th17) cells were determined by flow cytometric analysis. From the results, a sum of differentially expressed 186 genes (120 upregulated and 66 downregulated) and 104 proteins (73 upregulated and 31 downregulated) were identified. The Gene Ontology and KEGG pathway analyses indicated that CNV were mainly associated with immune and inflammatory responses, such as cellular response to IFN-β and Th17 cell differentiation. Moreover, the key nodes of the protein-protein interaction network mainly involved upregulated proteins, including alpha A crystallin and fibroblast growth factor 2, and verified by western blotting. To confirm the changes in gene expression, real-time quantitative PCR was performed. Furthermore, significantly decreased IFN-β was detected in both retina and plasma of CNV groups compared with controls as measured by enzyme-linked immunosorbent assay. IFN-β treatment significantly reduced CNV lesion size and promoted the proliferation of Th17 cells in laser-treated mice. Collectively, this study demonstrates that the occurrence of CNV might be associated with the dysfunction of immune and inflammatory processes, and IFN-β could serve as a potential therapeutic target.